OPTIMALISASI KEMAMPUAN METAKOGNISI MAHASISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN PRESTASI BELAJARNYA - Jumanto Jumanto (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2017)
This classroom action research aimed to improve students' learning achievement through enhancing students' metacognition ability in understanding the material of students' development. The study was conducted due to the unsatisfactory learning achievement of the students that did not meet the expected competency standards. The pre-intervention scores of the students were 2.70% in the excellent category (A), 27.03% in the moderate category (B), 64.86% in the sufficient category, and the rest were below the standard. The research subjects were 49 second-semester students consisting of 31 students from the Elementary School Teacher Education (PGSD) study program and 18 students from the Informatics Engineering Education (PTI) program. The sampling technique used was saturated sampling. The success indicator was determined by the action declared successful if the average value was above 75 and the number of students who passed the minimum mastery criteria (KKM) was more than 80%. Qualitative descriptive analysis was used to analyze the data. The research findings showed that the application of the cooperative learning model could improve students' learning achievement in understanding the material of students' development through enhancing their metacognitive abilities.